Ağ Toplumunda Sosyalleşme ve Yabancılaşma - Karagülle, Ayşegül Elif; Çaycı, Berk (The Turkish Online Journal of Design Art and Communication, 2014)
Deployment of internet to billions of people in the last decade; use of networking in all fields of life; it’s all occur with the convergence of Internet and mobile communications (Castells, 2007: 246).Within this period, increasing of social networks’ popularity, performing of all kinds of communication via networking, a new process of socialization. These developments have affected individuals relations, communications, process of socialization, individuals of life style and interaction with the environment. Each technology are occured social transformation on societies. Especially communication technologies inflict transformations on habits, cultures, business lives, education systems of societies. Lifestyles which ensue with modernization, cause disappear of traditional social order. Transformations brought about by modernity have been more effective than the other (Giddens, 2012; s. 12). Breaking traditional communication ways and communicating on social networks, brings social alienation and loneliness. With the diffusion of social communication; individuals can’t find time for face to face communication. According to David Harvey; with the development of communication technologies and means of transport, obstacles to globalization are eliminated. In this way, communication is provided instantly, owing to lose time and space’s importance. This situation causes time-space compression. Individual’s communication with their environment and with the world, occurs via information technologies. Depending on these developments; habits, thoughts, feelings have been changed and concepts have ensued which are referred to virtual life, virtual behavior and virtual culture. In this context, individuals are driven to loneliness because of the changings in their social life. This situation leads them to the process of alienation and loneliness. As long as social networks don’t replace face to face communicatin,it can enrich individuals’ social life. However, when social communication takes place of face to face communication, virtual environment and virtual communication have occured. Social networks, as a new social environment is considered to be the most appropriate places for modern societies. Socialization via social networks is going to discussed in context of the relationship between technology and society. At the same time, in this article will be emphasized on being passive in the face of technology.
Keywords: Modernleşme; Yalnızlaşma; Yabancılaşma; İnternet Bağımlılığı; Modernization; Lonelyness; Alienation; Internet Addiction